Environmental Reflexivity, Youth Participation, and Inclusive Sustainability Education: Learning from School-Based Waste Bank Initiatives - Sheren Cyntia Kim; Leo Nardion; Martinus Danang Pamungkas; Cindy Xavier (Universitas Muhammadiyah Surakarta, 2026)
Although the environmental crisis has emerged as a global issue, student involvement in environmental activism remains restricted. This study aims to examine the background and forms of environmental reflexivity of students of Maitreyawira High School, Batam, who are involved in the Baswira waste bank program. This study used a qualitative approach to collect data through observation, in-depth interviews, and document analysis of eight participants. The results show that the background and the nature of the students’ activities were derived from their daily experience and social interaction in the waste bank activities. Consequently, ecological consciousness and responsible behaviour towards the environment have developed gradually. The waste bank programme also functions as a social space for inclusive learning and encourages students to participate actively in sustainability practices. This study highlights the significance of the practical potential of school-based environmental education for the formation of environmental responsibility and the development of sustainable communities.